Grass 2 Cash @Scale Project: Western Uganda regional multistakeholder workshop report - Sibiko, Kenneth W; Kimbugwe, Paul; Mwema, Emmanuel; Mwendia, Solomon; Ohmstedt, Uwe; Notenbaert, An (2022)
This report details the proceedings of the Grass 2 Cash @Scale project multistakeholder meeting, organized by the Alliance of Bioversity International and CIAT at Lake View Hotel, Mbarara, on April 21-22, 2022. This hybrid meeting included 19 participants from various organizations such as ABC, MAAIF, SNV-TIDE, NARO, dairy farmers, Simlaw seeds, and local governments from Mbarara, Kabale, and Kabarole. The workshop aimed to develop a common understanding of the project objectives, refine the Theory of Change, validate monitoring and learning protocols, and draft an activity plan. The event featured presentations, plenary discussions, and interactive breakout sessions.